Experimental Kinetics Study on Diethyl Carbonate Oxidation - Sean P. Cooper; Claire M. Grégoire; Yousef M. Almarzooq; Eric L. Petersen; Olivier Mathieu (Fuels, 2023)
Diethyl carbonate (DEC) is a common component of the liquid electrolyte in lithium ion batteries (LIBs). As such, understanding DEC combustion chemistry is imperative to improving chemical kinetic modeling of LIB fires. To this end, a comprehensive experimental study was conducted to collect ignition delay times, CO time histories, and laminar flame speeds during DEC combustion. Ignition delay times were collected using a heated shock tube at real fuel–air conditions for three equivalence ratios (ϕ = 0.5, 1.0, and 2.0) near atmospheric pressure and for temperatures between 1182 and 1406 K. Another shock tube was used to collect CO time histories using a laser absorption diagnostic. These experiments were conducted for the same equivalence ratios, but highly diluted in argon and helium (79.25% Ar + 20% He) at an average pressure of 1.27 atm and a temperature range of 1236–1669 K. Finally, a heated constant-volume vessel was used to collect laminar flame speeds of DEC at an initial temperature and pressure of 403 K and 1 atm, respectively, for equivalence ratios between 0.79 and 1.38. The results are compared with different mechanisms from the literature. Good agreement is seen for the ignition delay time and flame speed measurements. However, significant deviations are observed for the CO time histories. A detailed discussion of the chemical kinetics is presented to elucidate the important reactions and direct future modeling efforts.